‘Doing good by proxy’: Human-animal kinship and the ‘donation’ of canine blood - Ashall, Vanessa; Hobson-West, Pru (Wiley, 2017)
This paper demonstrates the relevance of animals to medical sociology by arguing that pet owners’ accounts of veterinary decision-making can highlight key sociological themes which have important relevance to both human and animal health. Based on semi-structured interviews, the paper argues that interspecies ‘kinship’ allows for the extension of sociological claims regarding altruism, self-interest and mutuality from human blood donation to companion animal blood ‘donors’. Furthermore, this study extends sociological understanding of the human-animal bond by showing how the dog’s status as kin meant they were expected to donate blood, and that the act of donation itself represents an important opportunity for family ‘display’. However, owners who do not or cannot donate blood themselves describe pet blood donation as an opportunity to lessen associated feelings of guilt or obligation through ‘doing good by proxy’. These findings raise critical sociological and ethical questions concerning the risks and benefits of donation, and for how we understand third-party decision making. Finally, the paper argues for the close entanglement of human and animal health, and concludes that sociologists of health and medicine should explore the radical possibility that decision-making in healthcare more generally might be influenced by experiences at the veterinary clinic, and vice versa.